0 like 0 dislike

0 like 0 dislike
$$\huge\boxed{\bf\:x = \frac{3}{4}}$$

Step-by-step explanation:

$$5x - 2(x+1)=\frac{1}{4}$$

Use the distributive property for 2(x + 1).

$$5x - 2x - 2= \frac{1}{4}$$

Subtract 2x from 5x.

$$3x - 2= \frac{1}{4}$$

Bring 2 to the right hand side of the equation .

$$3x = \frac{1}{4} + 2$$

$$3x = \frac{1}{4} + \frac{8}{4} \: \: [LCM = 4]\\3x = \frac{9}{4}$$

Now, bring 3 to the right hand side of the equation .

$$x = \frac{9}{4} \times \frac{1}{3}\\x = \frac{9}{12}\\\boxed{\bf\:x = \frac{3}{4}}$$

▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬
by
0 like 0 dislike
Delaney solve for X by isolating it, or getting it by it self

Step-by-step explanation:

5x−2(x+1)=1/4 (distribute the 2)

5x-2x - 2 = 1/4 (subtract 2x from 5x)

3x -2 +2 = 1/4 +2 (add 2 to both sides)

3x = 2_1/4 (put 2 & 1/4 together)

3x = 9/4 (convert 2_1/4 to 9/4)

$$\frac{1}{3}$$*3*x = $$\frac{1}{3}$$*$$\frac{9}{4}$$ ( mutilply both sides by 1/3)

X = 3/4 (cross multiply )

There you go

X = $$\frac{3}{4}$$
by